1998
DOI: 10.1161/01.cir.98.14.1431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Platelet Activation on Coronary Collateral Blood Flow

Abstract: Background-The platelet products thromboxane A 2 and serotonin have been shown to cause constriction of welldeveloped coronary collateral vessels. This study was performed to determine whether intravascular platelet activation produced with platelet activating factor (PAF) can cause a decrease in coronary collateral blood flow. Methods and Results-Collateral vessel growth was induced by embolization of a hollow stainless steel plug into the left anterior descending coronary artery (LAD) of adult dogs. The anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In addition, Mohan et al [22] suggested that exposure to Hcy could induce platelet activation and hypercoagulability. Since platelet activating factor can reduce reducing coronary blood flow [23], these results indicate that Hcy may affect hemodynamics.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, Mohan et al [22] suggested that exposure to Hcy could induce platelet activation and hypercoagulability. Since platelet activating factor can reduce reducing coronary blood flow [23], these results indicate that Hcy may affect hemodynamics.…”
Section: Discussionmentioning
confidence: 82%
“…PAF is an important phospholipid with diverse physiological and pathological roles in vivo, including effects on circulation (5,22,30). Due to its potent actions on blood vessels, PAF might be a putative mediator in ischemic brain injury (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…PAF exerts its effects by interacting with a specific PAF receptor (30). Depending on the species and tissues, PAF causes constriction or dilation according to different coupling mechanisms (5,22,26). For instance, PAF is a potent constrictor of cerebral arterioles in newborn pigs (5) and produces vasodilatation in mesenteric circulation in dogs (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations